Light absorbing organic aerosols (brown carbon) over the tropical Indian Ocean: impact of biomass burning emissions - Bikkina Srinivas; M M Sarin (Environmental Research Letters, 2013)
The first field measurements of light absorbing water-soluble organic carbon (WSOC), referred as brown carbon (BrC), have been made in the marine atmospheric boundary layer (MABL) during the continental outflow to the Bay of Bengal (BoB) and the Arabian Sea (ARS). The absorption signal measured at 365 nm in aqueous extracts of aerosols shows a systematic linear increase with WSOC concentration, suggesting a significant contribution from BrC to the absorption properties of organic aerosols. The mass absorption coefficient ( b _abs ) of BrC shows an inverse hyperbolic relation with wavelength (from ∼300 to 700 nm), providing an estimate of the Angstrom exponent (α _P , range: 3–19; Av: 9 ± 3). The mass absorption efficiency of brown carbon (σ _abs−BrC ) in the MABL varies from 0.17 to 0.72 m ^2  g ^−1 (Av: 0.45 ± 0.14 m ^2  g ^−1 ). The α _P and σ _abs−BrC over the BoB are quite similar to that studied from a sampling site in the Indo-Gangetic Plain (IGP), suggesting the dominant impact of organic aerosols associated with the continental outflow. A comparison of the mass absorption efficiency of BrC and elemental carbon (EC) brings to focus the significant role of light absorbing organic aerosols (from biomass burning emissions) in atmospheric radiative forcing over oceanic regions located downwind of the pollution sources.